Differential Expression of Paraburkholderia phymatum Type VI Secretion Systems (T6SS) Suggests a Role of T6SS-b in Early Symbiotic Interaction - Hug, Sebastian; Liu, Yilei; Heiniger, Benjamin; Bailly, Aurélien; Ahrens, Christian H.; Eberl, Leo; Pessi, Gabriella (Frontiers in Plant Science, 2021)
Paraburkholderia phymatum STM815, a rhizobial strain of the Burkholderiaceae family, is able to nodulate a broad range of legumes including the agriculturally important Phaseolus vulgaris (common bean). P. phymatum harbors two type VI Secretion Systems (T6SS-b and T6SS-3) in its genome that contribute to its high interbacterial competitiveness in vitro and in infecting the roots of several legumes. In this study, we show that P. phymatum T6SS-b is found in the genomes of several soil-dwelling plant symbionts and that its expression is induced by the presence of citrate and is higher at 20/28°C compared to 37°C. Conversely, T6SS-3 shows homologies to T6SS clusters found in several pathogenic Burkholderia strains, is more prominently expressed with succinate during stationary phase and at 37°C. In addition, T6SS-b expression was activated in the presence of germinated seeds as well as in P. vulgaris and Mimosa pudica root nodules. Phenotypic analysis of selected deletion mutant strains suggested a role of T6SS-b in motility but not at later stages of the interaction with legumes. In contrast, the T6SS-3 mutant was not affected in any of the free-living and symbiotic phenotypes examined. Thus, P. phymatum T6SS-b is potentially important for the early infection step in the symbiosis with legumes.